Responses of Dental Pulp Cells to a Less Invasive Bleaching Technique Applied to Adhesively Restored Teeth - Soares, Diana Gabriela [UNESP]; Sacono, Nancy Tomoko; Ribeiro, Ana Paula Dias; Basso, Fernanda Goncalves [UNESP]; Scheffel, Debora Sales [UNESP]; Hebling, Josimeri [UNESP]; Souza Costa, Carlos Alberto de [UNESP] (Quintessence Publishing Co Inc, 2015)
Purpose: To assess the cytotoxicity of 35% hydrogen peroxide (HP) bleaching gel applied for 15 min to sound or restored teeth with two-step self-etching adhesive systems and composite resin.Materials and Methods: Sound and restored enamel/dentin disks were stored in water for 24 h or 6 months + thermocycling. The disks were adapted to artificial pulp chambers and placed in compartments containing culture medium. Immediately after bleaching, the culture medium in contact with dentin was applied for 1 h to previously cultured odontoblast-like MDPC-23 cells. Thereafter, cell viability (MTT assay) and morphology (SEM) were assessed. Data were analyzed by two-way ANOVA and Tukey's test (alpha = 5%).Results: In comparison to the negative control group (no treatment), no significant cell viability reduction occurred in those groups in which sound teeth were bleached. However, a significant decrease in cell viability was observed in the adhesive-restored bleached groups compared to negative control. No significant difference among bleached groups was observed with respect to the presence of restoration and storage time.Conclusion: The application of 35% HP bleaching gel to sound teeth for 15 min does not cause toxic effects in pulp cells. When this bleaching protocol was performed in adhesive-restored teeth, a significant toxic effect occurred.
Keywords: laboratory research; toxicity; odontoblasts; tooth bleaching; adhesives